Water Dimension of BRICS Cooperation: National Challenges and Joint Opportunities - A. Likhacheva; H. Kalachyhin; S. Abdolova; N. Kamenkovich (BRICS Law Journal)
This article examines the evolution and potential of the water agenda of BRICS. The members of this international association of major countries of South America, Eurasia, Asia and Africa are rich in water resources and population. The development of water resources extends beyond their borders to projects in other countries through the activities of a major development institution, the New Development Bank of BRICS. Such conditions suggest some anticipation of a global and comprehensive view on the part of BRICS on the issues relating to water resources. However, the hypothesis of this article is opposite: despite the unique potential of the BRICS water strategy, it remains non-specific, focused on the lower common denominators for the member countries such as cleanliness, sanitation and water management. To account for this, the authors take the position that the bureaucratic logic of basic common interest downgrades strategic vision. This is reflected in the growing gap between the multifaceted nature of the issues related to water resources in the world and the narrowly specialized approach of BRICS association which perceives water de facto without its resource and global function. To study this, the authors analyze the water portfolios of the BRICS member countries and compare the national water agendas based on an analysis of policy documents. They then systematize water initiatives under the auspices of the BRICS and, finally, calculate virtual water flows and their structure between the BRICS countries using agricultural products trade as an example. The conducted analysis allows the authors to identify a wide gap between the current and potential water agenda of the BRICS. The authors then propose a number of initiatives that can create added value for the BRICS as an association both for its member countries and for developing countries facing water resource challenges. The authors assert that such a new approach, based on a profound understanding of the resource function of water as a commodity with global value, has all the potential to be implemented by BRICS.